Pre-spawning water temperature affects sperm respiration and reactivation parameters in male carps - Boryshpolets, Sergey; Dzyuba, Boris; Drokin, Sergey (Fish physiology and biochemistry, 2009)
Concentration, ability to motility, motility during the second activation (reactivation), and endogenous respiration were studied in sperm from two experimental groups of carp males. Group 1 was maintained for 7 days at 15 degrees C (cold water (CW) group), whereas the second group was subjected to a temperature of 20 degrees C (warm water (WW) group) before sperm sampling. Reactivation were achieved after incubation of firstly activated sperm in media with osmotic pressure adjusted up to 300 mOsm*kg(-1) by increasing K(+) concentration. Statistically significant reduction of spermatozoa concentration in CW samples versus WW (from 46.0 +/- 12.5 (15 degrees C) to 59.3 +/- 7 10(9) (20 degrees C) spermatozoa /ml) have been observed. The sperm of the CW group required a significantly longer incubation time (37 min) under isotonic conditions to achieve a maximum percentage of potent motility at repeated activation than the WW group (23 min). After activation of sperm motility, an increase of respiration rate up to maximum level has been found, this level remained the same under condition of recovering the potential to repeated activation. During the sperm movement respiration rate, in CW group (6.1 nmol O(2)/min/10(9)spermatozoa) and WW (3.9 nmol O(2)/min/10(9)spermatozoa), was significant higher compared to nonactivated sperm (2.4 nmol O(2)/min/10(9)spermatozoa for CW and 1.1 nmol O(2) /min/10(9)spermatozoa for WW). And keeping males for 7 days at 15 degrees C increase the respiration rate of sperm.
Keywords: neparametrická statistika; spermie; Temperature; buněčné dýchání; kapři; Oxygen Consumption; Sperm Motility; teplota; zvířata; časové faktory; Carps; motilita spermií; Male; spotřeba kyslíku; Statistics, Nonparametric; Spermatozoa; Animals; mužské pohlaví; Time Factors; Cell Respiration